A new efficient cross-layer relay node selection model for Wireless Community Mesh Networks. (July 2017) - Zhao, Liang; Al-Dubai, Ahmed; Li, Xianwei; Chen, Guolong; Min, Geyong
Highlights: Packet Priority-Oriented routing metric and Packet Priority-oriented QoS routing metric are the first to provide differentiated priorities and service levels to applications with different needs. PPO considers the application priority. PP-QoS considers the channel busy level to improve the performance of path selection. Abstract: Current networking technologies are not perfectly equipped to support Quality of Service (QoS), which is vital for real-time multimedia applications in Wireless Community Mesh Networks (WCNs). Therefore, there is a need to devise innovative routing algorithms to support QoS on top of existing standards. Thus, this paper presents a cross layer relay node selection model for routing protocols in order to offer optimal routes to real-time applications. To the best of our knowledge, our two proposed routing metrics, Packet Priority-Oriented routing metric (PPO) and Packet Priority-oriented QoS routing metric (PP-QoS), are the first to provide differentiated priorities and service levels to applications with different needs. PPO considers the application priority. Moreover, PP-QoS also considers the channel busy level to improve the performance of path selection. The simulation confirms the superiority of the proposed model against a number of existing counterparts. Graphical abstract: